PENGARUH PENGETAHUAN PENGGUNAAN ALCOHOL-BASED HAND SANITISER TERHADAP HIDRASI KULIT PADA MAHASISWA FK UPN VETERAN JAKARTA ANGKATAN 2017 - Jiyi Malikah Adilah (2020)
Alcohol-based hand sanitizer is a part of hand hygiene, that function as an alternative of hand washing with water and soap. The use of alcohol-based hand sanitizer has rise along with COVID-19 outbreak. Improper use of alcohol-based hand sanitizer intentionally or unintentionally can have an impact on the skin. This is because the alcohol contained in alcohol-based hand sanitizer has the ability to denaturate protein and reduce enzyme activity in stratum corneum. This study aims to determine the effect of knowledge on the use of alcohol-based hand sanitizer on skin hydration in FK UPN Veteran Jakarta Students class of 2017. This study is analytic observational non-experimental with cross sectional approach. The sample is 75 students. The study instrument used a questionnaire to assess both knowledge (cronbach alpha 0.641) and skin hydration (cronbach alpha 0.814). The research shows that the majority of FK UPN Veteran Jakarta class of 2017 sutdents have good knowledge (97.3%) and lack of skin hydration (65.3%). Data analysis using Fisher's alternative test showed that there is no significant effect between knowledge on the use of alcohol-based hand sanitizer and skin hydration in FK UPN Veteran Jakarta Students class of 2017 in August 2020 (p=o.541; 95% CI 1.310-1.842). This can happen because the effect size is low.